2022
DOI: 10.1177/17590914221131446
|View full text |Cite
|
Sign up to set email alerts
|

Defibrinogenation Ameliorates Retinal Microgliosis and Inflammation in A CX3CR1-Independent Manner

Abstract: Microglia-mediated inflammation plays a significant role in neuronal and vascular damage in diabetic retinopathy (DR), but the mechanism linking inflammation, neurodegeneration, and impaired vascular integrity is still unclear. Previous studies from diabetic mouse models showed accumulation of fibrinogen at vessel lesions surrounded by perivascular microglial clusters. The purpose of this study was to evaluate whether the pathological hallmarks of gliosis and vascular aberrations characterized in diabetic anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 61 publications
(77 reference statements)
1
7
0
Order By: Relevance
“…6 F, I) revealed a reduction in microglial activation associated gene clusters ( Ly86 , Cx3cr1 , Siglech , Clec7a , Trem2 , Fcgr3 , Csf1r , Fcrg1 ) indicative that these changes in microglia morphology correlate with transcriptional reprograming. Additionally, it was shown that fibrinogen depletion using the defibrinogenating agent Ancrod, ameliorated reactive microgliosis and release of proinflammatory cytokines in the diabetic retina [ 45 ]. Complementary to these findings, depleting microglia reduced fibrinogen deposition in the diabetic retina (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…6 F, I) revealed a reduction in microglial activation associated gene clusters ( Ly86 , Cx3cr1 , Siglech , Clec7a , Trem2 , Fcgr3 , Csf1r , Fcrg1 ) indicative that these changes in microglia morphology correlate with transcriptional reprograming. Additionally, it was shown that fibrinogen depletion using the defibrinogenating agent Ancrod, ameliorated reactive microgliosis and release of proinflammatory cytokines in the diabetic retina [ 45 ]. Complementary to these findings, depleting microglia reduced fibrinogen deposition in the diabetic retina (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Four months diabetic mice ( Figure 2 ) did not receive LPS treatment, due to their increased sensitivity to cachexia at this more chronic stage of diabetes. Acute LPS treatment can cause hypoglycemia and induce large variation in circulating glucose levels in diabetic mice ( 37 , 38 ). Therefore, to avoid large fluctuations in glucose levels and to prevent masking hyperglycemia, 10 weeks diabetic mice, ( Figures 3 – 5 and Supplementary Figures 2 – 6 ) received one daily injection of 0.08mg/kg LPS for 2 consecutive days prior to euthanasia as previously characterized ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…A visual acuity assessment, featuring a two-choice discrimination task (Fig. 5 A, B) was utilized to determine if mice could distinguish between two distinct visual cues [ 5 , 29 ]. ND WT and FKN KO PBS-treated animals were tested under visible and infrared light to establish a baseline of visual acuity readouts.…”
Section: Resultsmentioning
confidence: 99%
“…Individually housed mice were food deprived to 85% of their ad libitum body weight to increase motivation for the task. During the food deprivation period, mice were shaped to search for food reward and a cocoa puff (Cocoa Krispies, Kellogg’s) buried in a 30 mL cup, which limited their food intake prior to the commencement of the experiment [ 5 ]. Both the food pellet and the cocoa cereal crumb were hidden under cumin-scented, fine-grain woodchip bedding (Sani-Chip 146 IRR, LabSupply), to prevent the use of olfactory/reward associations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation